Maximum power extraction in solar renewable power system - a bypass diode scanning approach. (August 2018) - Winston, D. Prince; Kumar, B. Praveen; Christabel, S. Cynthia; Chamkha, Ali J.; Sathyamurthy, Ravishankar
Highlights: The proposed method uses individual panel's bypass diode voltage drop to find the partial shading level. Achieving global maximum power point under partial condition with minimum tracking time. 100% accuracy in tracking the GMPP. Maximum energy extraction from the solar PV system. Simulation is done for 3 × 3 and 10 × 10 PV array. Hardware verification is done for 3 × 3 PV array. The tracking speed of the proposed method is almost same for any number of PV array configurations. Abstract: The effectiveness of solar energy as a viable energy source is hampered by various factors including high cost of components and lowered operating efficiency due to partial shading. Partial shading reduces the output of not only the shaded part of the panel but also the other panels connected to the same photovoltaic (PV) array. This paper discusses the benefits of using a bypass diode based voltage drop measurement and maximum power point tracking (MPPT) system in the power generation of a PV array. An algorithm to find the global maximum power in short span of time is also presented. MATLAB is then used to perform the simulation of the proposed algorithm on a 3 × 3 photovoltaic array and the results are checked against actual outdoor tests to test the validity of the proposed method. The proposed method holds even when extended to any array combinations for practical applications.